2016
DOI: 10.18632/oncotarget.8985
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA PARROT is an upstream regulator of c-Myc and affects proliferation and translation

Abstract: AbstrAct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Among them, long noncoding RNAs (lncRNAs) have been widely implicated in post-transcriptional gene expression regulation. The expression level of lncRNAs is usually very low and tissue-specific[ 121 ]. c-MYC can regulate the expression of lncRNAs, some of these may also contribute to the transcription of c-MYC target genes[ 122 ].…”
Section: Anti-cancer Therapeutic Aspects Of C-myc In the Colonmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, long noncoding RNAs (lncRNAs) have been widely implicated in post-transcriptional gene expression regulation. The expression level of lncRNAs is usually very low and tissue-specific[ 121 ]. c-MYC can regulate the expression of lncRNAs, some of these may also contribute to the transcription of c-MYC target genes[ 122 ].…”
Section: Anti-cancer Therapeutic Aspects Of C-myc In the Colonmentioning
confidence: 99%
“…PARROT has been also identified as an upstream regulator of c-MYC. Its depletion results in the depletion of c-MYC mRNA and protein expression, subsequently altering cell growth and proliferation[ 121 ]. In gastric cancer c-MYC activates the expression of colon cancer associated transcript 1 (CCAT1) lncRNA, leading to an increased proliferation and migration of cancer cells[ 123 ].…”
Section: Anti-cancer Therapeutic Aspects Of C-myc In the Colonmentioning
confidence: 99%
“…Liu et al have indicated that miR-18b inhibits TGF-β1-induced HFSc differentiation into smooth muscle cells by targeting SMAD2, which provided novel insights into the regulatory mechanisms of TGF-β-induced differentiation of HFSc (31). In addition, the lncRNA PARROT is regarded as a regulator of c-Myc and upregulates proliferation and translation of human mammary epithelial cells (32). We reported that PlncRNA-1 transfection increased Wnt signaling pathway downstream effectors Axin2, CyclinD1 and Myc gene expression in HFSc compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNA studies reported senescence-suppressing results connecting to c-Myc. LncRNA PARROT, an upstream modulator of c-Myc, is downregulated in the senescence of human mammary epithelial cells [137]. c-Myc may transcriptionally activate some lncRNAs, such as USP2-AS1, to inhibit senescence and improve the proliferation of lung cancer cells [138].…”
Section: Akt Effector (C-myc)-regulating Lncrnas and Cell Functionsmentioning
confidence: 99%